1995
DOI: 10.1128/jvi.69.12.8155-8158.1995
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus induction of recombinase-activating genes RAG1 and RAG2

Abstract: In experimental B-cell infections, Epstein-Barr virus induced sustained expression of V(D)J recombinase-activating genes RAG1 and RAG2, whose aberrant activity has been implicated in chromosomal translocations in B-cell neoplasms. In cell lines in which RAG1 and RAG2 were detected, virus integrated into cellular DNA rather than assumed the configuration of extrachromosomal episomes. Expression of the Epstein-Barr virus nuclear antigen 1 in transient transfection assays was sufficient to induce both recombinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…HindIII digested DNA of the Raji clones did not produce comparably different-sized hybridizing fragments (data not shown). Thus, EBV genomes in HU-untreated Raji and -treated Raji clones are not integrated into the host cell DNA through the TR [Delecluse et al, 1993;Srinivas and Sixbey, 1995], and this nonintegrated status is not altered in HU-treated Raji clones.…”
Section: Intracellular Forms Of Ebv Genome In Raji Cellsmentioning
confidence: 96%
“…HindIII digested DNA of the Raji clones did not produce comparably different-sized hybridizing fragments (data not shown). Thus, EBV genomes in HU-untreated Raji and -treated Raji clones are not integrated into the host cell DNA through the TR [Delecluse et al, 1993;Srinivas and Sixbey, 1995], and this nonintegrated status is not altered in HU-treated Raji clones.…”
Section: Intracellular Forms Of Ebv Genome In Raji Cellsmentioning
confidence: 96%
“…EBNA-1 initiates DNA replication at the latent replication origin, oriP, and maintains EBV DNA molecules in cells by binding to a specific DNA sequence in oriP (Middleton & Sugden, 1992). In addition to modulation of EBV latent promoters, transient expression of EBNA-1 is sufficient to induce the recombinase-activating genes RAG1, RAG2 (Srinivas & Sixbey, 1995) and CD25 (interleukin 2 receptor a-chain; Kube et al, 1999) in cell lines. However, the mechanism whereby EBNA-1 regulates the expression of these cellular genes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, non-specific single-stranded binding properties are also a functional property shared with the catalytic regions of Tc element transposases (van Luenen et al 1994). (Jones et al 1992, Srinivas & Sixbey 1995 and T lymphocytes (this work) may reflect shared promoter sequences between the BALF-2 ORF and the RAG sequences.…”
Section: Evidence That the Balf-2 Protein Is A Viral Homologue Of Thementioning
confidence: 64%
“…Up-regulation of RAG-1 and RAG-2 expression has also been demonstrated in EBV-infected cord blood cells and B-cell lines (Jones ct al. 1992, Srinivas & Sixbey 1995. Others have found that some EBV-transformed B-cell lines demonstrate a high level of expression of RAG-1 and RAG-2 (Kuhn-Hallek et al 1995).…”
Section: Importance Of the Linear To Circular Genome Transition In Ebmentioning
confidence: 99%